AN ANALYSIS OF SENTENCE FRAGMENT FOUND IN STUDENTS WRITING PARAGRAPH - Yuliarsih; Laili Amalia (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
Study writing become a challenge one, because their need as student strive to be produce a good paragraph but the reality sometimes they make an error in their paragraph. One of the error is fragment. Fragment is incomplete sentence. This research is aimed to identify some fragment in student’s writing paragraph and what is source of the error that occurred in students’ writing. It is descriptive qualitative. The participant data in this research is taken from 25 students. The researcher used class X A in senior high school Wachid Hasyim year 2021/2022 as sample. The result of this study showed the most common fragment found in their subject and complete verb are omitted is the highest , the second position is a dependent clause fragment is the second, the third rank is the verb is omitted and the last position is the subject is omitted with. Moreover the questionnaire showed that the incomplete knowledge of English is the source of student’s errors.